Defining the Realized Niche of the Two Major Clades of Trichodesmium: A Study on the West Florida Shelf - Confesor, Kristina A.; Selden, Corday R.; Powell, Kimberly E.; Donahue, Laura A.; Mellett, Travis; Caprara, Salvatore; Knapp, Angela N.; Buck, Kristen N.; Chappell, P. Dreux (Frontiers in Marine Science, 2022)
The cyanobacterium Trichodesmium plays an essential role supporting ocean productivity by relieving nitrogen limitation via dinitrogen (N2) fixation. The two common Trichodesmium clades, T. erythraeum and T. thiebautii, are both observed in waters along the West Florida Shelf (WFS). We hypothesized that these taxa occupy distinct realized niches, where T. thiebautii is the more oceanic clade. Samples for DNA and water chemistry analyses were collected on three separate WFS expeditions (2015, 2018, and 2019) spanning multiple seasons; abundances of the single copy housekeeping gene rnpB from both clades were enumerated via quantitative PCR. We conducted a suite of statistical analyses to assess Trichodesmium clade abundances in the context of the physicochemical data. We observed a consistent coastal vs. open ocean separation of the two clades: T. erythraeum was found in shallow waters where the concentrations of dissolved iron (dFe) and the groundwater tracer Ba were significantly higher, while T. thiebautii abundance was positively correlated with water column depth. The Loop Current intrusion in 2015 with entrained Missisippi River water brought higher dFe and elevated abundance of both clades offshore of the 50 m isobath, suggesting that both clades are subject to Fe limitation on the outer shelf. Whereas, previous work has observed that T. thiebautii is more abundant than T. erythraeum in open ocean surface waters, this is the first study to examine Trichodesmium niche differentiation in a coastal environment. Understanding the environmental niches of these two key taxa bears important implications for their contributions to global nitrogen and carbon cycling and their response to global climate change.